Identifying Neogobius species from the southern Caspian Sea by otolith shape (Teleostei: Gobiidae) - Davoodi, Parisa; Rahimian, Hassan (Zootaxa, 2016)
Three Neogobius species are common in the southern Caspian Sea. Identification of these species, especially from remains, is not fully understood. The present study compares the morphological characteristics of sagittal otoliths of N. caspius, N. pallasi and N. melanostomus. Furthermore, it also provides a dichotomous identification key based on otoliths morphology.